2012
DOI: 10.1016/j.bbamcr.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for activation of mutated p53 by apigenin in human pancreatic cancer

Abstract: Pancreatic cancer is an exceedingly lethal disease with a five-year survival that ranks among the lowest of gastrointestinal malignancies. Part of its lethality is attributable to a generally poor response to existing chemotherapeutic regimens. New therapeutic approaches are urgently needed. We aimed to elucidate the anti-neoplastic mechanisms of apigenin-an abundant, naturally-occurring plant flavonoid-with a particular focus on p53 function. Pancreatic cancer cells (BxPC-3, MiaPaCa-2) experienced dose and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 26 publications
1
32
1
Order By: Relevance
“…Wu et al (2014) proved that apigenin (30 mg/kg) oral administration inhibited pancreatic cancer tumour growth in xenograft nude mice model implanted with human pancreatic cancer cell line AsPc-1, on which apigenin showed anti-proliferative effect with an IC50 value of 28.5 µM in vitro. King et al (2012) also found that apigenin suppressed orthotopic pancreatic tumour growth in nude mice fed with a diet supplemented with 0.2% apigenin (w/w). Apigenin fed mice had remarkably elevated levels of apigenin detected in both plasma and pancreas, and no significant degradation of apigenin was detected even over 72 hours.…”
Section: Apigenin Induces Ros Accumulation In Pancreatic Cancer Cellsmentioning
confidence: 93%
“…Wu et al (2014) proved that apigenin (30 mg/kg) oral administration inhibited pancreatic cancer tumour growth in xenograft nude mice model implanted with human pancreatic cancer cell line AsPc-1, on which apigenin showed anti-proliferative effect with an IC50 value of 28.5 µM in vitro. King et al (2012) also found that apigenin suppressed orthotopic pancreatic tumour growth in nude mice fed with a diet supplemented with 0.2% apigenin (w/w). Apigenin fed mice had remarkably elevated levels of apigenin detected in both plasma and pancreas, and no significant degradation of apigenin was detected even over 72 hours.…”
Section: Apigenin Induces Ros Accumulation In Pancreatic Cancer Cellsmentioning
confidence: 93%
“…Specific to PDAC, TP53 gene mutations occur in more than 75% of patients and are shown to contribute to proliferation and even drive metastasis through gain of function activities (Iacobuzio-Donahue and Herman, 2014; Weissmueller et al, 2014). Previous studies have shown that exogenous delivery of p53 sensitizes PDAC to chemotherapy (Camp et al, 2013), treatment with adenovirus encoding p53 sensitizes PDAC to radiation (Li et al, 2013), and the use of small molecules like apigenin (King et al, 2012) or mouse double minute 2 homolog (MDM2) inhibitors (Azmi et al, 2010) can restore endogenous p53 function and slow PDAC proliferation. Although VSV encoding p53 has never been studied in PDAC cells, VSV-driven murine p53 gene expression resulted in enhanced antitumor activities in vivo against mammary adenocarcinoma (Heiber and Barber, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrates that apigenin induces apoptosis via downregulation of NF-κB, Akt and Bcl-2 and that mice show lower tumour volume after dietary apigenin treatment [7,84]. Kaempferol inhibits cell growth and induces apoptosis in pancreatic cancer cell lines [7,85].…”
Section: Flavonoidsmentioning
confidence: 99%